Hearing loss in workers exposed to different type of noise - ZAMYSŁOWSKA-SZMYTKE, Ewa; KOTYŁO, Piotr; BĄK, Marek; FUENTE, Adrian; ŚLIWIŃSKA-KOWALSKA, Mariola (Archives of Acoustics, 2007)
It's well documented that noise damages peripheral part of the auditory tract (cochlea). Only few investigations were performed to assess central hearing disturbances caused by noise on animal.The aim of the study was to evaluate the site of hearing damage in 2 groups of individuals exposed to different types of noise. First group consisted of 62 dockyard workers exposed to impulsive noise with co-exposure to hand-arm vibration while second group included 76 bottle glass factory workers exposed to continuous steady-state noise. Results were referred to 86 control subjects exposed neither to noise nor vibrations.Pure-tone audiometry, immitance audiometry, Auditory Brainstem Response (ABR) and cognitive-event relate auditory evoked potentials (wave P-300) were performed in all subjects.Audiometric results revealed the poorest hearing level in dockyard workers among all groups. The bottle factory workers had also significant hearing impairment at high frequencies as compared to controls. Although the wave V at the ABR was prolonged in the dockyard workers this change could reflect sensorineural hearing thresholds shift and retrocochlear damage. The latency of P-300 wave was prolonged in dockyard workers exclusively suggesting a cortical effect of exposure to impulsive noise.Conclusions. Exposure to high level impulsive noise in combination with hand-arm vibration may cause hearing deficit greater than expected. Abnormalities involve peripheral and central auditory system. More observations are necessary to confirm these findings.